Apical versus basal ventricular entrainment in supraventricular tachycardia - Dhaifallah Yahya Yahya Moqbil; Amir Mohamed Abdelwahab; Essam Baligh Eweis; Mohamed Zaki Elramly (Cairo : Dhaifallah Yahya Yahya Moqbil, 2010)
Differentiation between AVNRT and AVRT can be sometimes challenging. Apical right ventricular (RV) entrainment can help in differentiation, however it has some fallacies. We thought to compare the accuracy of basal RV entrainment to RV apical entrainment in identifying the mechanism of SVT
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Cardiology
Issued also as CD
Keywords: Cardiology; Electrophysiology service; Supraventricular tachycardia